A fast and effective algorithm based on improved hough transform - Dongfeng, Ren; Qiubing, Wang; Fujun, Sun (Journal of the Indian Society of Remote Sensing, 2016)
Comparing to those problems of High complexity and endpoint being difficult to be detected in traditional Line Detection Algorithm Based on Hough Transform, a fast and effective straight line extraction algorithm based on improved Hough Transform(HT) is put forward. First, a reduction sequence parameter array for the cumulative parameter matrix need to establish in proposed algorithm; then the parameter track line is established by analyzing the first parameter of the array, and with the parameter track line the endpoint of the line can be confirmed and the line is extracted. Eventually, the experimental results show that principle of the algorithm is simple, which can effectively solve the traditional HT problems, such as the not high enough accuracy, the complex calculation. Meanwhile the algorithm which is suitable for parallel processing is robust to handle different types of the image data.